Practices in Peptic Ulcer Bleeding Controversies among University- Versus Nonuniversity-Affiliated Gastroenterologists - Justin Cheung; Grant Sawisky; Robert Enns; Michael F Byrne; Qiaohao Zhu; Clarence KW Wong (Canadian Journal of Gastroenterology)
BACKGROUND: Practices relating to acute peptic ulcer bleeding (APUB) outside of guideline recommendations are unknown.